Efficacy and Impact of Key Performance Indicators as Perceived by Key Informants in Ontario Universities - Chan, Vivian (Canadian Journal of Higher Education, 2015)
The Ontario Ministry of Education and Training’s Task Force on University Accountability first proposed key performance indicators (KPIs) for colleges and universities in Ontario in the early 1990s. The three main KPIs for Ontario universities are the rates of (1) graduation, (2) employment, and (3) Ontario Student Assistance Program loan default. This exploratory and descriptive study examined the perceptions of 12 key informants from 11 participating universities about the efficacy and effectiveness of these KPIs. The results of this study demonstrate that a clear majority of participants believe these KPIs are not having the intended impact. This paper analyzes the evidence and makes recommendations designed to foster efficient collaboration between stakeholders; it also asks all parties to clarify their goals, agreed expectations, and requirements, in order to develop effective measures of institutional performance and accountability and address the political needs of the government, the universities, and the public.